Effect of drip irrigation regimes on yield and quality of field grown bell pepper - Sezen S.M.; Yazar A.; Eker S. (Water saving in Mediterranean agriculture and future research needs [Vol. 1], 2007)
In this study, carried out in 2002 and 2003 in Turkey, three irrigation intervals (I1:18-22 mm, I2:38-42 mm and I3:58-62 mm of cumulative pan evaporation from Class A pan) and three plantpan coefficients (Kcp1=0.50, Kcp2=0.75 and Kcp3=1.00) were evaluated. Irrigation intervals varied from 3-6 days in I1, 6-11 days in I2 and 9-15 days in I3 treatments. Maximum and minimum yields were obtained from the I1Kcp3 and I3Kcp1 treatments as 33140 kg ha-1 and 21620 kg ha-1 in 2002 and 35298 kg ha-1 and 21010 kg ha-1 in 2003, respectively. As the Kcp value decreased the total yields each irrigation interval also decreased. However, with the lower irrigation frequency (I3), lower yields were obtained with all Kcp coefficients. Seasonal water use values in the treatments varied from 365 mm in I2Kcp1 to 528 mm in I1Kcp3 in 2002 and 309 mm in I3Kcp1 to 511 mm in I1Kcp3 in 2003. Significant second degree polynomial relations were found between pepper yield and total water use. Water use efficiency (WUE) and irrigation water use efficiency (IWUE) values were influenced by the irrigation intervals and plant-pan coefficients. WUE ranged from 4.7 kg m-3 in I3Kcp2 to 7.6 kg m-3 in the I1Kcp1 in the 2002 growing season and ranged from 6.4 kg m-3 in I3Kcp3 to 7.9 kg m-3 in the I2Kcp2 in the 2003 growing season. Maximum IWUE was observed in I1Kcp1, and minimum IWUE was in I3Kcp3 treatment in the 2002 and 2003 growing seasons. Both Kcp coefficients (irrigation amounts) and irrigation frequencies had different effects on quality parameters such as number of fruit, mean fruit weight, pepper length and width, as well as stem diameter and plant height at harvest. In conclusion, I1Kcp3 irrigation regime is recommended for field grown bell pepper.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)